Malignant transformation of proliferative Verrucous Leukoplakia—systematic review & meta-analysis - Khadijah Mohideen; Snehashish Ghosh; Chandrasekaran Krithika; Mutaz Ali-Hassan; Revant Chole; Safal Dhungel (BMC Oral Health)
Abstract Background Proliferative Verrucous Leukoplakia (PVL) presents a unique manifestation of Oral Leukoplakia, characterized by its notable propensity for rapid advancement, dynamic clinical and histopathological alterations, and heightened risk of malignant transformation. Aim The present systematic review explores the demographic characteristics, risk factors, progression patterns, treatment preferences, and outcomes for PVL lesions that undergo malignant transformation. Materials and methods An electronic search was executed across various databases, such as PubMed, Scopus, Science Direct, Web of Science and Wiley Online Library from 1985 to December 2023, focusing on studies of PVL malignant transformation. Data on demographics, clinical features, treatment, and outcome data were synthesized, with bias assessed using Joanna Briggs Institute Criteria and outcomes evaluated using Comprehensive Meta-Analysis version (CMA) 3.0 software. Results Among 998 articles, 53 met inclusion criteria, covering 1159 PVL patients, with 48.4% experiencing malignant transformation over an average 6.28 ± 3.73—year follow-up. Most cases had low or moderate bias risk. In the malignant group, females comprised 74.3% of cases, with a mean age of 66.23 ± 7.76 years and had a 1.96 times greater risk of developing cancer (OR 1.96, 95% CI 1.38—2.782; p = 0.001). Gingiva (20%) and gingiva/buccal mucosa (17.4%) were commonly affected. Tobacco and alcohol showed weak associations, with most patients being non-smokers (59.54%) and non-drinkers (78.18%). HPV and candida infection positivity were tested in only a few studies and noted in a limited number of cases (33.3% and 38.46%, respectively). Malignant transformation mainly was invasive carcinoma (86.8%). Surgery was the primary treatment (58.33%), with 55.56% recurrence in 162 cases of data availability on recurrence. Of 228 patients with data availability, 33.77% succumbed to oral cancer from PVL-related oral cancer. Conclusions PVL, a rare variant of leukoplakia, poses a significant risk of cancer, emphasizing the need for vigilant monitoring and proactive treatment. It mainly affects elderly females without typical cancer risk factors. Understanding its etiology could aid early detection and management.